THE DEVELOPMENT OF ENGLISH FOR SPECIFIC PURPOSES SYLLABUS FOR FIRST YEAR STUDENTS OF SPECIAL EDUCATION AND REHABILITATION - Ivančević Otanjac, Maja (Specijalna edukacija i rehabilitacija, 2014)
This paper describes the development of the appropriate English for Specific Purposes (ESP) syllabus and course book for first year students of Special Education and Rehabilitation at the University of Belgrade. The syllabus was designed with regard to the students’ needs, their former knowledge of general English, and the available learning conditions. It focuses on professional vocabulary relevant to all 6 different departments of Special Education and Rehabilitation at the University of Belgrade. The grammar practiced corresponds to the B1 level as defined by the Common European Framework of Reference for Languages, since the entry level of most Special Education first year students is between A2 and B1. The developed syllabus fulfils the main aims of this ESP course – it repeats and practices appropriate general English structures, and familiarizes the students with key professional vocabulary they will need in further education.